Nazis and good neighbors - Friedman, Max Paul (Cambridge University Press, 2003)
This book is an exposé of a secret American operation during World War II to seize 4,000 Germans from Latin America and intern them in camps in the Texas desert. Rather than Nazi spies and saboteurs, they turned out to be a broad range of German immigrants, even Jewish refugees, most of whom posed no danger to national security. Research in seven countries reveals the diplomatic intrigues and human impact of a misguided policy that offers important lessons about US relations with Latin America, the failure to rescue victims of the Holocaust, and the treatment of civilians in wartime.